Leading innovation, creativity and enterprise - Cook, Peter (Bloomsbury Information, an imprint of Bloomsbury Publishing Plc, 2016)
"Drawing upon cutting edge research from academia but expressed clearly and concisely for the busy person seeking practical inspiration, Leading Innovation, Creativity and Enterprise will feature numerous case examples from companies such as Virgin, Pfizer, Roche and Fuji Film. The book deals with questions such as: What are the roots of creativity and imagination? How can we create the physiological and mental states under which creativity happens naturally rather than having to rely on creative thinking tools? What kind of leadership is required to make creativity and innovation business as usual behaviours in your enterprise? What is the role of technique in engendering creativity within teams? What are the most effective and reliable recipes for team based creativity? What ensures that creativity turns into innovation? What stops it? In exploring these questions, the book will show you how to produce and lead creative teams, as well as build an innovative company culture." - Resumé vydavatele
Keywords: kreativita; inovace; inovační podnikání; týmová práce; creative ability; innovations; innovative business; team work; studie; elektronické knihy; studies; electronic books